Temporal and spatial evolution characteristics of fracture distribution of floor strata in deep coal seam mining. (February 2022) - Hu, Yanbo; Li, Wenping; Chen, Xinmin; Xu, Hongzhong; Liu, Shiliang
Highlights: Monitoring of deep rock fracture by distributed optical fiber sensor. The time–space evolution characteristics of the mining floor fracture were revealed. Provide the basis for the prevention and control of mine confined water hazard. Abstract: With the increase in mining coal seam depth year by year, the high-pressure karst water hazard of coal seam floor poses a serious threat to mine safety. To solve this karst water disaster beneath the coal seam floor, it is necessary to Prevention-control the water-conducting passages developed in coal seam floor strata. Therefore, mathematical model analysis and Brillouin optical time domain reflection technology (BOTDRT) were used in this study to monitor the microstrain of floor rock in deep coal seam mining, and other methods were used to elucidate the mechanism of floor failure in deep coal seam mining. The results show that the maximum depth of floor rock breakage in coal seam mining is near the peak stress propagation line in front of the coal wall of coalface and reveals the stacking uplift of floor rock in goaf. Based on the measured data of preburied metal cable-based distributed optical fiber sensor (MCDOFS), the time–space evolution characteristics of floor breakage in coal seam mining and the law of floor breakage were revealed more finely. This study provides a basis for the prevention and control of high confined water hazard of limestone in a coal seam floor in deep seam mining.